Poder e memória em infância de Graciliano Ramos - MOURA, Ida Rosa Soares de (2020)
This research seeks to identify the marks of the exercise of the passage of power within the Childhood Romance of Graciliano Ramos, from the Foucaultian studies on the docilization of the bodies urged by the punishment processes. The relationships of memorial writing and how this memory mechanism remains and is told by the autobiographer. The connectors of understandings, the election and preservation of the facts to be counted; highlighting the change of power in the institution called the family and, above all, in social relations. The childhood of a lonely boy and confusion amidst a traditional and patriarchal family and the birth of the great writer. That brings in the paints of his writing the colors of the universe where he was born and grew docilization by the punishments and sanctions to which he was submitted. From a very hard childhood, within a large family, the marks of power from the point of view of standardization.